Exploring the Impact of Customer-Centric Strategies on Customer Loyalty in Merged Banks in Nepal - Kandel, Madan (Journal of Business and Social Sciences, 2024)
This study investigates the impact of a merger between Commercial Bank and a major regional bank in Nepal on Customer Satisfaction (CS), focusing on key drivers such as Agility (A), Customer-Centricity (CC), Consistency (C), and Accessibility (ACC). The research employs a descriptive and causal-comparative design, gathering data from 300 respondents through structured questionnaires. Descriptive statistics, correlation analysis, and multiple regression models were used to analyze the relationship between these factors and customer satisfaction. The findings reveal that all key drivers—Agility, Customer-Centricity, Consistency, and Accessibility—significantly influence Customer Satisfaction, with Agility and Customer-Centricity showing the strongest correlations (r = 0.80, p < 0.01 and r = 0.82, p < 0.01, respectively). The regression analysis demonstrates that these variables, including their interaction terms, account for a significant portion of the variance in customer satisfaction (R² = 0.842). The study concludes that improving agility and adopting a customer-centric approach are vital for enhancing customer satisfaction post-merger. The results emphasize the importance of seamless integration of services and effective communication during mergers to maintain customer trust. This research provides valuable insights for banks undergoing mergers, suggesting that attention to service quality and accessibility can help mitigate customer dissatisfaction.